Melanoma-derived cytokines and extracellular vesicles are interlinked with macrophage immunosuppression - Shankar Suman; Wendy K. Nevala; Alexey A. Leontovich; James W. Jakub; Liyi Geng; Sarah A. McLaughlin; Svetomir N. Markovic (Frontiers in Molecular Biosciences)
Cytokines play a crucial role in mediating cell communication within the tumor microenvironment (TME). Tumor-associated macrophages are particularly influential in the regulation of immunosuppressive cytokines, thereby supporting tumor metastasis. The upregulation of Th2 cytokines in cancer cells is recognized for its involvement in suppressing anticancer immunity. However, the association between these cytokines and tumor-secreted extracellular vesicles (EVs) remains poorly understood. Therefore, our objective was to investigate the connection between tumor-promoting macrophages and melanoma-derived EVs. The analysis from altered cytokine profile data showed that melanoma-derived EVs upregulate Th2 cytokine expression in naïve macrophages, thereby contributing to the promotion of tumor-supporting functions. Notably, many of these cytokines were also found to be upregulated in metastatic melanoma patients (n = 30) compared to healthy controls (n = 33). Overall, our findings suggest a strong connection between melanoma secretory EVs and the induction of tumor-associated macrophages that facilitates the development of an immunosuppressive TME, supporting melanoma metastasis through regulation at both local and systemic levels.